100 skill-building lessons using 10 favorite books - Lunsford, Susan (New York : Scholastic, 2001)
Contains one hundred lessons based on ten favorite children's books designed to help students meet important learning goals in reading, writing, and mathematics.
"A teacher's treasury of irresistible lessons & activities that help children meet learning goals in reading, writing, math & more.".
"Grades 1-3"--Cover.
Includes bibliographical references.
Professional
Keywords: Creative activities and seat work; Teaching -- Aids and devices; Creative activities; Teaching -- Aids and devices